2013
DOI: 10.1186/1297-9716-44-126
|View full text |Cite
|
Sign up to set email alerts
|

Lineage specific antigenic differences in porcine torovirus hemagglutinin-esterase (PToV-HE) protein

Abstract: Hemagglutinin-esterases (HE) are viral envelope proteins present in some members from the toro-, corona- and orthomyxovirus families, all related with enteric and/or respiratory tract infections. HE proteins mediate reversible binding to sialic acid receptor determinants, very abundant glycan residues in the enteric and respiratory tracts. The role of the HE protein during the torovirus infection cycle remains unknown, although it is believed to be important in the natural infection process. The phylogenetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…The HE gene of BToV can be genetically divided into two lineages, the BRV and B150 lineages [ 53 , 89 ]. A full-length genome analysis of five PToVs showed that they can be divided into two lineages, the Malkelo and P4 lineages, based on the HE gene [ 80 , 90 , 91 ], but not other genes [ 53 ] ( Figure 3 b). The two lineages may have been separated by an HE recombination event [ 89 ], and their common ancestor reportedly emerged 56 years ago [ 80 ].…”
Section: Genomementioning
confidence: 99%
“…The HE gene of BToV can be genetically divided into two lineages, the BRV and B150 lineages [ 53 , 89 ]. A full-length genome analysis of five PToVs showed that they can be divided into two lineages, the Malkelo and P4 lineages, based on the HE gene [ 80 , 90 , 91 ], but not other genes [ 53 ] ( Figure 3 b). The two lineages may have been separated by an HE recombination event [ 89 ], and their common ancestor reportedly emerged 56 years ago [ 80 ].…”
Section: Genomementioning
confidence: 99%
“…It is a class I membrane protein, and a member of the receptor destroying enzyme (RDE) protein family. There are two main domains identified in the monomer: the enzymatic acetyl-esterase region (E); and the receptor binding or lectin domain (25). The HE protein specifically but reversibly binds to mucopolysaccharides, mediating adhesion of virions to the intestinal wall.…”
Section: Etiologymentioning
confidence: 99%
“…It could be seen that this ELISA method had a high sensitivity, but its specificity may be slightly worse. The indirect ELISA based on PToV-HE protein is less sensitive and may have false negative results because of the diversity of HE proteins and the antigenic differences between HE lineages (14, 25). Development of other ELISA diagnostic methods based upon the PToV S protein is needed, according to experiences from porcine coronavirus such as porcine epidemic diarrhea virus (PEDV) (41).…”
Section: Diagnostic Assaysmentioning
confidence: 99%
“…the RNAdependent RNA polymerase [RdRp] and the helicase [Hel] amongst others) [1,10,14,15]. The rest of the viral genome harbors ORFs encoding structural proteins: spike (S) [16,17], membrane (M) [18,19], hemagglutinin-esterase (HE) [20][21][22], and nucleocapsid (N) [14,23], which are individually expressed from a nested set of 3'-coterminal subgenomic mRNAs [11,24,25].Accumulating evidence from different positive-strand RNA viruses indicates that in this heterogeneous group of viruses, genome replication and transcription invariably occur in close association with highly modified cellular membranes of diverse origins [26][27][28]. In fact, the presence of double membrane vesicles (DMVs) in the cytoplasm of cells infected with different nidoviruses has been associated with the formation of their replication and transcription complexes (RTCs) [29][30][31][32][33][34][35].…”
mentioning
confidence: 99%
“…the RNAdependent RNA polymerase [RdRp] and the helicase [Hel] amongst others) [1,10,14,15]. The rest of the viral genome harbors ORFs encoding structural proteins: spike (S) [16,17], membrane (M) [18,19], hemagglutinin-esterase (HE) [20][21][22], and nucleocapsid (N) [14,23], which are individually expressed from a nested set of 3'-coterminal subgenomic mRNAs [11,24,25].…”
mentioning
confidence: 99%